2011
DOI: 10.1021/ef200728r
|View full text |Cite
|
Sign up to set email alerts
|

Anisole and Guaiacol Hydrodeoxygenation over Monolithic Pt–Sn Catalysts

Abstract: Direct vapor-phase upgrading of biomass pyrolysis products requires a catalytic reactor able to treat high reactant flow rates without generating a large pressure drop, because conventional pyrolysis reactors operate near atmospheric pressure. Monolithic catalysts exhibit important advantages that make them good candidates for this purpose. In this paper, low-surface-area Inconel monoliths were coated with in-situ-grown carbon nanofibers (CNFs), which were subsequently impregnated with catalytic species (Pt, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
178
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(192 citation statements)
references
References 39 publications
7
178
0
4
Order By: Relevance
“…In the work of Prasomsri et al [36] the corresponding reactivity was the following: diphenyl > anisole > guaiacol > phenol > o-cresol [36]. Thus, dehydroxylation of the phenyl ring is difficult [37,39,48,61]. Reactivity of anisole higher than guaiacol reported in [39] similarly to the work of Prasomsri et al [36], can be explained by a higher bond dissociation energy required for the aromatic hydroxyl compared to methoxyl (Table 3).…”
Section: Comparative Studies Of a Single Feed Reactant Over The Same mentioning
confidence: 68%
See 2 more Smart Citations
“…In the work of Prasomsri et al [36] the corresponding reactivity was the following: diphenyl > anisole > guaiacol > phenol > o-cresol [36]. Thus, dehydroxylation of the phenyl ring is difficult [37,39,48,61]. Reactivity of anisole higher than guaiacol reported in [39] similarly to the work of Prasomsri et al [36], can be explained by a higher bond dissociation energy required for the aromatic hydroxyl compared to methoxyl (Table 3).…”
Section: Comparative Studies Of a Single Feed Reactant Over The Same mentioning
confidence: 68%
“…MoO3/ZrO2, 60 bar, benzene [39], 9. Pt-Sn/CNF/Inconel, 1 bar, benzene [48], 10. Ni-catalyst, 1.7 bar, benzene [50], for guaiacol: 11.…”
Section: Conversion and Main Products In The Hdo Of Lignin-derived Momentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been reported that double-oxygen compounds were much more prone to coke formation than single-oxygen compounds [115]. The HDO of anisole and guaiacol conducted by González-Borja and Resasco also suggested that more severe catalyst deactivation was observed with guaiacol relative to anisole [88]. In addition to reactant structures, catalyst properties such as acidity play an important role in coke formation.…”
Section: Catalyst Deactivationmentioning
confidence: 99%
“…Production of fuels from biomass is a considerable alternate and the thermochemical treatment is a valid approach for efficient biomass conversion. Pyrolysis of biomass gives bio-oil, a process that is relatively well developed (Mortensen et al [3], González-Borja and Resasco [4], Sun et al [5]). Chemical instability, small miscibility with hydrocarbons, corrosiveness, more amount of water and oxygen contents and low heating values are however the major drawbacks of bio-oil, which impede its direct application as the fuel (Saidi et al [6], Nimmanwudipong et al [7]).…”
Section: Introductionmentioning
confidence: 99%